2010
DOI: 10.1007/s11269-010-9592-1
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Evaluation of Pressurized Irrigation in Canal Commands

Abstract: India has one of the largest and most ambitious irrigation programme in the world with net irrigated area exceeding 47 million hectares. However, the overall project efficiency from the headwork to the farmer's field has been quite low which leads to not only poor utilization of irrigation potential created at huge cost, but also aggravates the degradation of soil and water resources and thereby endangers the sustainability of agricultural production system. As the cost of creating additional irrigation potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…Kumar et al (2009) found that integration of rainwater harvesting and gravity-fed micro-irrigation systems is an effective method of water management for growing vegetables. Srivastava et al (2010) observed that irrigation efficiency can be increased up to 95% by replacing the irrigation method from conventional (border or furrow) to pressurized irrigation. Micro-irrigation has wide adaptability in semi-arid and arid regions where water supply remains limited (Cetin et al, 2004;Singh et al, 2001Singh et al, , 2007.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kumar et al (2009) found that integration of rainwater harvesting and gravity-fed micro-irrigation systems is an effective method of water management for growing vegetables. Srivastava et al (2010) observed that irrigation efficiency can be increased up to 95% by replacing the irrigation method from conventional (border or furrow) to pressurized irrigation. Micro-irrigation has wide adaptability in semi-arid and arid regions where water supply remains limited (Cetin et al, 2004;Singh et al, 2001Singh et al, , 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, an auxiliary reservoir becomes an important component in planning of micro-irrigation systems especially when canal water supply is intermittent. An auxiliary reservoir is a storage structure (pond/tank) constructed in the canal irrigated area allowing farmers to store precious canal water and use it more judiciously through micro-irrigation for crop production (Kumar et al, 2008;Srivastava et al, 2010). Sometimes, during a lean period (a period with low demand for canal water) or in the rainy season when canal water is not required for irrigation of crops, it can be easily stored in an auxiliary reservoir for use during critical periods through the microirrigation system (Kumar et al, 2008;Kumar and Singh, 2010;Singh et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Later Shrivastava et al (2010), presented a study on feasibility of pressurized irrigation in canal command area.…”
Section: Feasibility Of Pressurized Irrigation In Command Areamentioning
confidence: 99%
“…We used financial discounted criteria such as the benefitcost ratio (BCR), net present value (NPV) and internal rate of return (IRR). The current study adopted the following equations to estimate the BCR, NPV and IRR criteria (Srivastava et al, 2010;Patil and Poddar, 2016;Borrego-Marín and Berbel, 2019):…”
Section: Introductionmentioning
confidence: 99%